Exposure to Allergen Causes Changes in NTS Neural Activities after Intratracheal Capsaicin Application, in Endocannabinoid Levels and in the Glia Morphology of NTS. (19th March 2015) - Spaziano, Giuseppe; Luongo, Livio; Guida, Francesca; Petrosino, Stefania; Matteis, Maria; Palazzo, Enza; Sullo, Nikol; de Novellis, Vito; Di Marzo, Vincenzo; Rossi, Francesco; Maione, Sabatino; D'Agostino, Bruno
Abstract : Allergen exposure may induce changes in the brainstem secondary neurons, with neural sensitization of the nucleus solitary tract (NTS), which in turn can be considered one of the causes of the airway hyperresponsiveness, a characteristic feature of asthma. We evaluated neurofunctional, morphological, and biochemical changes in the NTS of naive or sensitized rats. To evaluate the cell firing activity of NTS, in vivo electrophysiological experiments were performed before and after capsaicin challenge in sensitized or naive rats. Immunohistochemical studies, endocannabinoid, and palmitoylethanolamide quantification in the NTS were also performed. This study provides evidence that allergen sensitization in the NTS induced: (1) increase in the neural firing response to intratracheal capsaicin application, (2) increase of endocannabinoid anandamide and palmitoylethanolamide, a reduction of 2-arachidonoylglycerol levels in the NTS, (3) glial cell activation, and (4) prevention by a Group III metabotropic glutamate receptor activation of neural firing response to intratracheal application of capsaicin in both naïve and sensitized rats. Therefore, normalization of ovalbumin-induced NTS neural sensitization could open up the prospect of new treatments based on the recovery of specific brain nuclei function and for extensive studies on acute or long-term efficacy of selective mGlu ligand, in models of bronchial hyperreactivity.